Helicobacter pylori infection and arteriosclerosis - Tamara Anna Rakszewska; Adam Alzubedi (Kazimierz Wielki University, 2019)
The hypothesis regarding the relationship between Helicobacter pylori infection and the development of arteriosclerosis is not clearly demonstrated and needs validation even though many clinical trials conducted in this area in recent years seem to support this etiopathology. H. pylori is a Gram-negative, microaerophilic bacterium, usually found in the stomach, widespread in the environment. Infections often occurs even in early childhood. As a result of infection a chronic inflammation develops with concomitant elevated levels of C-reactive protein (CRP). It has long been known that atherosclerosis is a chronic disease of the arteries with underlying inflammation. The formation of atherosclerotic plaques may also begin in childhood. There are more than one mechanism that may affect disease development. Lipopolysaccharides of H. pylori by stimulating the secretion of Tumor Necrosis Factor (TNF) by macrophages inhibits lipoprotein lipase activity, which results in an increase in serum triglycerides and a decrease in serum High-density Lipoprotein (HDL) cholesterol. The second mechanism leading to an increased risk of arteriosclerosis may be associated with a chronic inflammation of the gastric mucosa which may lead to impaired absorption of many nutrients, including vitamins B6, B12 and folic acid, the deficiency of which results in secondary hyperhomocysteinemia. Elevated levels of homocysteine ​​are a strong risk factor for atherosclerosis. Lastly, in the serum of patients with H. pylori infection, elevated values ​​of number of important factors from the point of view of atherosclerotic plaques formation are found. These include CRP, interleukin 6 (IL-6), interleukin 8 (IL-8), TNF-α, fibrinogen, type 1 plasminogen tissue activator inhibitor and Willebrand factor. Taking into account the above-mentioned correlations, it seems reasonable to continue research focusing on many pathomechanisms that may help explaining the cause and relationship of H. pylori infection to the development of atherosclerosis. Clinical trials conducted on the pediatric population, could contribute to the broadening of medical knowledge in this area, as well as to the modification of preventive and therapeutic recommendations for atherosclerosis and its consequences.